Social identity loss and reverse culture shock: Experiences of international students in China during the COVID-19 pandemic - Raja, Rameez; Ma, Jianfu; Zhang, Miwei; Li, Xi Yuan; Almutairi, Nayef Shabbab; Almutairi, Aeshah Hamdan (Frontiers in Psychology, 2023)
Background: International students often expose to various challenges during their life transitions. The mindsponge mechanism suggests that individuals absorb and integrate new cultural values that are compatible with their core values and eject the least important ones. On the basis of this notion, the article explored the experiences of international students in China regarding their unplanned return to home countries during the COVID-19 pandemic. Aim: The study focuses on experiences of two groups of international students. 1) Those who remained in China during the pandemic, and 2) those who had left China and stranded in their home countries due to a ban on international travel amid COVID-19. Method: This qualitative study comprised of in-depth semi structured in-person and online interviews. Thematic Analysis was used to analyze the data in order to generate study themes. Results: The result revealed that students who remained in China experienced challenges that include no meeting with friends, closure of campuses, lockdown, parents’ concern regarding health issues and anxiety. On the hand, students, who had left China during the pandemic were stranded in their home countries. This group of students experienced severe problems than the students who remained in China. Since the transition to home countries was “unplanned”, they were not ready to adjust in native culture and were vulnerable to severe reverse culture shock. Upon returning to their home countries, international students faced a number of challenges, including readjustment in home countries and changes in their lives in host and home countries. In addition, they lost social and academic resources, such as disruption of study environment, losing important group memberships, financial constraints, visa expiry, graduation delay, and academics suspension. Conclusion: This study concluded that the international students experienced cultural problems after unplanned transition to their home countries during the pandemic. They described effects of reverse culture shock as being more distressing. They perceived dissatisfaction due to loss of previously held social identities and sense of belonging to the traditional society they left behind. There is a need of future studies on the long-term effect of unplanned transition on psychological, social and professional experiences.